2018
DOI: 10.3390/agronomy8100198
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Appropriate Spatial Resolution for the Meteorological Data for Regional Winter Wheat Potential Productivity Simulation in China Based on WheatGrow Model

Abstract: The crop model based on physiology and ecology has been widely applied to the simulation of regional potential productivity. By determining the appropriate spatial resolution of meteorological data required for model simulation for different regions, we can reduce the difficulty of acquiring model input data, thereby improving the regional computing efficiency of the model and increasing the model applications. In this study, we investigated the appropriate spatial resolution of meteorological data needed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…The WheatGrow model includes five modules, the apical and phenological development of wheat, photosynthesis and dry matter production, dry matter partitioning and organogenesis, yield and quality formation, and soil moisture and nutrition balance modules [21][22][23][24][25][26][27].The WheatGrow model can simulate wheat growth and development conditions under three growth conditions: yield potential, water limitation, and nitrogen limitation [22,30]. The WheatGrow model has been validated in simulations of winter wheat at multiple ecological observation sites throughout the main winter wheat production area of China using field experiment data from different sowing dates, plant densities, and nitrogen fertilization strategies, and it is reported that the WheatGrow model displays good agreement between the predicted and observed values and can effectively capture the spatial variations of the yield at different regional scales [4,34,35].…”
Section: Wheatgrow Model Description and Validationmentioning
confidence: 99%
See 4 more Smart Citations
“…The WheatGrow model includes five modules, the apical and phenological development of wheat, photosynthesis and dry matter production, dry matter partitioning and organogenesis, yield and quality formation, and soil moisture and nutrition balance modules [21][22][23][24][25][26][27].The WheatGrow model can simulate wheat growth and development conditions under three growth conditions: yield potential, water limitation, and nitrogen limitation [22,30]. The WheatGrow model has been validated in simulations of winter wheat at multiple ecological observation sites throughout the main winter wheat production area of China using field experiment data from different sowing dates, plant densities, and nitrogen fertilization strategies, and it is reported that the WheatGrow model displays good agreement between the predicted and observed values and can effectively capture the spatial variations of the yield at different regional scales [4,34,35].…”
Section: Wheatgrow Model Description and Validationmentioning
confidence: 99%
“…Yield potential refers to potential productivity, which is entirely determined by temperature and photosynthetically active radiation when nutrients, moisture, soils, cultivars, and other agricultural technological parameters are at optimum conditions [1,2]. Yield potential estimations at the regional scale can identify the variations in the upper yield limit, optimize the planting system, and improve the use efficiency of agroclimatic resources, thereby providing information for agricultural impact and risk assessment to support policymaking [1][2][3][4][5]. Additionally, the process-based crop growth model as a robust, generic, and cost-effective tool to simulate yields under a range of agricultural and climatic scenarios, in this context, crop growth models have been extensively used to estimate yield potentials over large areas.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations